Analysis of Technological advancements in Pakistani Automobile Car Industry. (Global Journals of Research in Engineering, 2011)
The auto market is one of the largest segments in world trade. The annual size of automotive export trade in the world has grown to a massive level of over US$ 600 billion, which accounts for about 10 percent of the world export. Changing models, improving fuel efficiency, cutting costs and enhancing user comfort without compromising quality are the most important challenges of the auto industry in a fastly globalizing world. Hence there is a need for exploring the industrial collaborations in this sector globally for better quality, favorable costs, fuel efficiency and attractive designs. Therefore, the requirement of information exchange is much more pronounced now then ever before for keeping the auto industry afloat and competitive.In third world countries, due to non availability of indigenous development, lack of necessary skill level and industrial infrastructure, no institutionalized set up appears to be available to back up the acquired technology and facilitate its absorption. The Pakistani Automobile Industry is amongst the fastest growing sector in national economy. Heavy investments have been made in establishing Automobiles assembling plants by various global automobile manufacturers during past few years. Under #x2018;The Auto Industry Development Programs#x2019;, through incentives offered by #x2018;The Government of Pakistan, deletion of automobiles spare parts up to a certain level is being carried out by automobile manufacturers depending upon the potential capabilities and infrastructure availability with the local vendors. The objective of this research is to understand the advantages attained by Pakistani automobile car assemblers and vendors, during last thirty years through mutual collaboration and technology acquisition from global automobile manufacturers.This paper also focuses on the deletion of spare parts of various locally assembled automobile cars by analyzing those vendors who are generating maximum revenues through production of these spare par